Business Model Canvas Strategy in Chicken Egg Farming Business PT. Galus Unggul Jaya - Wulan Ndari, Priska; Zumrotin (Profit: Jurnal Adminsitrasi Bisnis, 2025)
Galus Unggul Jaya is a company engaged in the chicken egg business livestock industry in Malang Regency. The problems faced are the number of competitors, production volume, and marketing reach at PT Galus Unggul, which are still not optimal, so a business development strategy is needed. This study aims to describe the development strategy for chicken egg businesses using the Business Model Canvas at PT Galus Unggul Jaya Malang. The method used in this study is qualitative descriptive research with data collection through observation, interviews, literature studies, and documentation. The results of this study indicate that, indirectly, PT. Galus Unggul Jaya has implemented 9 Business Model Canvas business models that have not been mapped. However, in its implementation, four elements still need to be proposed so that business development can run optimally, namely, in the elements of customer segments, channels, customer relationships, and key resources. The results of the strategy formulation using SWOT analysis show that PT. Galus Unggul Jaya can exploit opportunities and strengths to minimize weaknesses and threats.